Electrospun Ca3Co4−xO9+δ nanofibers and nanoribbons: Microstructure and thermoelectric properties. Issue 2 (20th October 2022) - Kruppa, Katharina; Maor, Itzhak I.; Steinbach, Frank; Beilin, Vadim; Mann‐Lahav, Meirav; Wolf, Mario; Grader, Gideon S.; Feldhoff, Armin
Abstract: Oxide‐based ceramics offer promising thermoelectric (TE) materials for recycling high‐temperature waste heat, generated extensively from industrial sources. To further improve the functional performance of TE materials, their power factor should be increased. This can be achieved by nanostructuring and texturing the oxide‐based ceramics creating multiple interphases and nanopores, which simultaneously increase the electrical conductivity and the Seebeck coefficient. The aim of this work is to achieve this goal by compacting electrospun nanofibers of calcium cobaltite Ca3 Co4− x O9+ δ, known to be a promising p‐type TE material with good functional properties and thermal stability up to 1200 K in air. For this purpose, polycrystalline Ca3 Co4− x O9+ δ nanofibers and nanoribbons were fabricated by sol–gel electrospinning and calcination at intermediate temperatures to obtain small primary particle sizes. Bulk ceramics were formed by sintering pressed compacts of calcined nanofibers during TE measurements. The bulk nanofiber sample pre‐calcined at 973 K exhibited an improved Seebeck coefficient of 176.5 S cm −1 and a power factor of 2.47 μW cm −1  K −2 similar to an electrospun nanofiber‐derived ceramic compacted by spark plasma sintering.